Representation Of Gender Pictured Out In “English In Mind Student’s Book 3” - Salsabila, Tasya; Perpisa, Lili; Sesmiyanti, Sesmiyanti (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research is motivated to understand how gender roles are portrayed in textbooks, especially in the context of English language teaching in accordance with the Merdeka Curriculum. This study aims to determine the gender representation in the English textbook titled